Analisis Kompetensi Guru dalam Memahami Konsep dan Praktik Penilaian dalam Pembelajaran di Sekolah - Eviana Hikamudin; Aryanti Aryanti; Dian Peniasiani; Rusdiono Muryanto; Burhan Kurniansyah (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Teachers' understanding of assessment concepts and practices is an important element in measuring of student learning outcomes, but in reality there are teachers not understand in assessment concept and practice it well. The purpose of this study was to measure the level of teacher understanding of assessment concepts and practicing it in learning. The method used in this study is descriptive analytics. The study sample was teachers from 3 elementary schools in Bandung Regency and surrounding areas. The results showed that as many as 57% of respondents understood the concept of assessment well and 57% of respondents could practice assessment well. The implication is the need to strengthen the understanding of concepts and assessment practices for teachers to improve their competence in learning. In addition, it is necessary to monitor and evaluate by the principal to improve the quality of learning in schools.